A systematic approach to studying the material cultural heritage (A reading into the nature of the Numidian royal shrines) - ben ferfoud, amine (The Algerian Historical Journal, 2026)
This research aims to know the nature of material heritage and the extent of its influence on our culture, which needs a new reading, to understand the patterns and behavior of those ancient human societies and their beliefs, and their attachment to authentic architectural art, and to search for its reflection in the present and the extent of the development of its artistic elements of a local character, and from the results we have reache the following : The Numidian royal shrines are considered important architectural landmarks in the map of local funerary architecture, upon which our hopes for searching for belonging, and the deep goy of our origins are committed. They also confirm the antiquity of human settlement and the existence of an ancient political system in the region.